Denotative and Connotative Meaning Used in Writing Poetry - Rulik Setiani (Edukasi Lingua Sastra, 2020)
The aimed of this article is to describe the use of denotative and connotative meaning in writing poetry. Writing as an activity carried out by someone in expressing thoughts, idea, and feeling through words. There are several kinds of writing activity that someone can do; one of them is writing poetry. Poetry is one of literary works besides prose and drama, poetry consists of stanzas, lines, rhythms, and rhymes. The meaning used in poetry usually uses two meanings, there are denotative and connotative meanings, and denotative meaning is literal or actual meaning of the word itself, while denotative meaning is a meaning that has a sense and emotional feeling of the word. By using connotative or figurative language, the poetry can be seen more beautiful and contains aesthetic effect. It is also used by the poet to convey something indirectly as variations in writing poetry.